Poly(Methyl methacrylate-co-butyl acrylate-co acrylic acid): Synthesis, characterization and targeted solid state-Dye sensitized solar cell application / R Shanti Rajantharan - R Shanti , Rajantharan (2018)
A series of polymeric solid state electrolytes (PSSE) was developed using ultra high molecular weight (UHMW) poly(methyl methacrylate-co-butyl acrylate-co-acrylic acid) [P(MMA-co-BA-co-AA)] targeted for solid-state dye-sensitized solar cell (DSSC). The copolymer was synthesized via emulsion polymerization and formulated as such that it possessed low glass transition temperature (Tg). For properties optimization, different ratios of MMA to AA were tested. All the analogous copolymers have similar bulk properties but their colloidal stabilities and conversion efficiencies vary. Among these, AA05 formulation [abbreviated as P(MMA-co-BA-co-AA) with (55 : 40 : 5) wt.%] has the highest monomer conversion and colloidal stability. The combination with other superior properties allows AA05 to be the most suitable matrix for PSSE development. The first PSSE system developed from the host AA05 was formulated by doping different amounts of sodium iodide (NaI, System I) into the matrix containing a fixed ratio of plasticizer mixture [ethylene carbonate (EC): propylene carbonate (PC) at 1:1 ratio] and iodine (I2). The complexation between NaI and AA05 increases the amorphicity, and causes the ionic conductivity (?) to rise up to 4.21 × 10?4 S cm?1 in NaI-PSSE containing 20 wt.% NaI (abbreviated as NaI-20) for solid film with thickness of 100 ?m. A photovoltaic efficiency, as high as 3.22 % under 1 Sun was recorded for the rubbery-PSSE (above Tg) containing 15 wt.% NaI (NaI-15; ? = 3.85 × 10?4 S cm?1). The utilization of rubbery-PSSE offers a number of appealing properties for device fabrication, such as (i) soft electrolyte film that forms good interfacial contact with dye-sensitized semiconductor such as titanium oxide (TiO2; photoanode) and (ii) high availability of free volume when the cell temperature at 50 °C (cell processing) is brought to 25 °C (cell working). Although good cell performance was successfully obtained, the ionic conductivity diminution in NaI-15 at increasing temperature near to its Tg =50 °C may have limited the cell performance. In order to eliminate this possibility, two additional PSSE systems (System II and III) were developed using NaI-15 as the control. System II contains higher concentration of EC: PC while System III contains dispersed fumed silica nanoparticles (SiO2 NPs). Enhancement of ionic conductivity was observed in both EC: PC and SiO2 NPs systems, with no drop in conductivity near to the Tg of highly conducting PSSE. This arises as the subsequent increase of amorphous content. Unfortunately, the PSSE developed from System II were not suitable for cell fabrication owing to its soft mechanical strength. The cell efficiency of System III (?= 6 % under 1 Sun in the presence of 2 wt.% SiO2) was enhanced by two folds as compared to that of NaI-15. The recorded value is comparable to that of gel polymer electrolyte (GPE) assembly. The fast ion tunneling along the highly conducting interface layer (grain boundary) of SiO2 NPs and high free volume availability (or amorphous phase) may explain the high photovoltaic performance. All the observations led us to believe that UHMW P(MMA-co-BA-co-AA) with AA05 formulation can be a good substitute for polymers with molecular weight ranges in hundreds of thousands.